Effect of Agnikarma in the Pain Management of Janu-Sandhigata Vata (Knee-Osteoarthritis) W.S.R to Inflammatory Biomarkers (hs-CRP, TNF-α and IL6)-An Open Labelled Clinical Trial - Vats, Himanshi; Shindhe, Pradeep Shahjirao; Kumbar, Vijay; Killedar, Ramesh Shivappa; Nadaf, Rubeen (Asian Journal of Biological and Life Sciences, 2025)
Background: Globally, Osteoarthritis (OA) is the most common cause of disability. The concept that OA is an inflammatory disease has experienced an enormous shift in the last several years. Research indicates that proinflammatory cytokines (TNF-α, IL-6, and hs-CRP) are important mediators in the pathophysiology of osteoarthritis. Janu-Sandhigata Vata, in which Shleshma avrata vata is primarily responsible for excruciating pain in the knee joint, is correlated with knee OA. Objectives: To evaluate the effect of Agnikarma on inflammatory biomarkers in the pain management of Osteoarthritis. Materials and Methods: The study was an open labelled clinical trial with a pre and post design. For the study, a total of 15 patients with knee osteoarthritis (Janusandhigata vata) who met the inclusion criteria were enrolled. The patients were treated with a single Agnikarma on the 2) most tender point of affected knee joint. Systemic venous blood was collected before the Agnikarma procedure, after 24 hr and after 1 week of the procedure to assess the changes in the inflammatory biomarkers by ELISA method. Parameters like VAS, VDS scale, Crepitus, Tenderness, Range of movements were assessed on baseline, immediately after the procedure, after 24 hr, 3rd day and after 1 week. Statistical analysis was done with Wilcoxon Matched Pair test, dependent ‘t’ test and one way ANOVA. Results: Comparing baseline to various time periods yielded significant results (p<0.0001) in all evaluated parameters. Conclusion: Agnikarma was found effective on inflammatory biomarkers and in the pain management of knee osteoarthritis.
Keywords: Agnikarma; hs-CRP; IL-6; Inflammatory Biomarkers; Inflammatory mediators; Janusandhigata vata; Osteoarthritis; Pain management; Para surgical procedure; TNF-α